2021
DOI: 10.7554/elife.70272
|View full text |Cite
|
Sign up to set email alerts
|

An essential, kinetoplastid-specific GDP-Fuc: β-D-Gal α-1,2-fucosyltransferase is located in the mitochondrion of Trypanosoma brucei

Abstract: Fucose is a common component of eukaryotic cell-surface glycoconjugates, generally added by Golgi-resident fucosyltransferases. Whereas fucosylated glycoconjugates are rare in kinetoplastids, the biosynthesis of the nucleotide sugar GDP-Fuc has been shown to be essential in Trypanosoma brucei. Here we show that the single identifiable T. brucei fucosyltransferase (TbFUT1) is a GDP-Fuc: β-D-galactose α-1,2-fucosyltransferase with an apparent preference for a Galβ1,3GlcNAcβ1-O-R acceptor motif. Conditional null … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 91 publications
(138 reference statements)
0
19
0
Order By: Relevance
“…The discovery that the biosynthesis of the nucleotide sugar GDP-fucose was required for parasite growth in T. brucei [76] and in Leishmania major [77], suggested that these organisms contain one or more essential FUT genes. A single GT11 family FUT, TbFUT1, was identified in the T. brucei genome and shown to be essential in BSF and PCF cells [78]. Similarly, the L. major orthologue (LmjFUT1) is essential for cell growth [79].…”
Section: Gt11 Family Fut1mentioning
confidence: 99%
See 4 more Smart Citations
“…The discovery that the biosynthesis of the nucleotide sugar GDP-fucose was required for parasite growth in T. brucei [76] and in Leishmania major [77], suggested that these organisms contain one or more essential FUT genes. A single GT11 family FUT, TbFUT1, was identified in the T. brucei genome and shown to be essential in BSF and PCF cells [78]. Similarly, the L. major orthologue (LmjFUT1) is essential for cell growth [79].…”
Section: Gt11 Family Fut1mentioning
confidence: 99%
“…Similarly, the L. major orthologue (LmjFUT1) is essential for cell growth [79]. The most curious feature of TbFUT1 and LmjFUT1 is their localisation to the parasite mitochondria [78,79]. Recombinant TbFUT1 has GDP-Fuc : βGal α1-2-fucosyltransferase activity, common amongst GT11 family enzymes, with an apparent preference for acceptor substrates containing a terminal LNB (Galβ1-3GlcNAc) motif [78].…”
Section: Gt11 Family Fut1mentioning
confidence: 99%
See 3 more Smart Citations